Poor mobilization of hematopoietic stem cells: definitions, incidence, risk factors, and impact on outcome of autologous transplantation - Wuchter, Patrick; Ran, Dan; Bruckner, Thomas; Schmitt, Thomas; Witzens-Harig, Mathias; Neben, Kai; Goldschmidt, Hartmut; Ho, Anthony Dick (Biology of blood and marrow transplantation, 2010)
As more efficient agents for stem cell mobilization are being developed, there is an urgent need to define which patient population might benefit from these novel drugs. For a precise and prospective definition of “poor mobilization” (PM), we have analyzed the efficiency of mobilization in patients intended to receive autologous transplantation at our center in the past 6 years. Between January 2003, and December 2008, 840 patients with the following diagnoses were scheduled to undergo leukapheresis: multiple myeloma (MM, n = 602) and non-Hodgkin lymphoma (NHL, n= 238). Most patients mobilized readily: close to 85% of the patients had a level of 20/μL to >500/μL of CD34+ cells at the peak of stimulation. Of the 840 patients, 129 (15.3%) were considered to be PMs, defined as patients who had a peak concentration of <20/μL of CD34+ cells upon stimulation with granulocyte-colony stimulating factor (G-CSF) subsequent to induction chemotherapy appropriate for the respective disease. Among them, 38 (4.5%) patients had CD34+ levels between 11 and 19/μL at maximum stimulation, defined as “borderline” PM, 49 (5.8%) patients had CD34+ levels between 6 and 10/μL, defined as “relative” PM, and 42 patients (5%) with levels of <5/μL, defined as “absolute” PM. There was no difference in the incidence of PM between patients with MM versus those with NHL. Sex, age, body weight (b.w.) and previous irradiation therapy did not make any significant difference. Only the total number of cycles of previous chemotherapy (P = .0034), and previous treatment with melphalan (Mel; P = .0078) had a significant impact on the ability to mobilize. For the good mobilizers, the median time to recovery of the white blood cells (WBCs) to 1.0/nL or more was 13 days with a range of 7 to 22 days, whereas for the PM group it was 14 days with a range of 8 to 37 days. This difference was statistically not significant. The median time to recovery of the platelets counts to an unmaintained level of >20/nL was 11 days with a range of 6 to 17 days for the good mobilizers, whereas for the PM it was 11 days with a range of 7 to 32 days. Again, this difference was not significant. The majority of the patients today intended for autologous transplantations were able to mobilize readily. As long as ≥2.0 × 106 of CD34+ cells/kg b.w. have been collected, PM was not associated with inferior engraftment.